2012
DOI: 10.1016/j.it.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The yin and yang of viruses and interferons

Abstract: Interferons (IFNs)-α/β are critical effectors of the innate immune response to virus infections. Through activation of the IFN-α/β receptor (IFNAR), they induce expression of IFN-stimulated genes (ISGs) that encode antiviral proteins capable of suppressing viral replication and promoting viral clearance. Many highly pathogenic viruses have evolved mechanisms to evade an IFN response and the balance between the robustness of the host immune response and viral antagonistic mechanisms determines whether or not th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 86 publications
(132 reference statements)
0
91
0
3
Order By: Relevance
“…Ribavirin, in combination with pegylated IFN-α, is the main treatment against Hepatitis C virus. However, IFN-α/β and ribavirin treatments are of relatively poor efficacy in vivo against most RNA viruses as they efficiently blunt IFN-α/β signaling through expression of virulence factors 5 and often escape ribavirin 3 . This added to the fact that ribavirin treatment is raising important toxicity issues, although it was recently approved against severe hRSV disease with controversial benefits 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Ribavirin, in combination with pegylated IFN-α, is the main treatment against Hepatitis C virus. However, IFN-α/β and ribavirin treatments are of relatively poor efficacy in vivo against most RNA viruses as they efficiently blunt IFN-α/β signaling through expression of virulence factors 5 and often escape ribavirin 3 . This added to the fact that ribavirin treatment is raising important toxicity issues, although it was recently approved against severe hRSV disease with controversial benefits 6 .…”
Section: Introductionmentioning
confidence: 99%
“…THs are able to enhance sensitivity of lymphocytes to interferons (IFN) and promote IFN-mediated cytotoxic activity of NK cells (Provinciali & Fabris, 1990;Provinciali et al, 1994). Interferons (i.e., , , and g) are small regulatory cytokines that were originally identified as anti-viral factors and play pivotal roles in immune responses to viral infection (Wang & Fish, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Data from recent studies have revealed that these hormones may also control the latency/reactivation and infectivity of viruses (HSV-1 in particular) via regulation of gene expression (Davis et al, 2011;Wang & Fish, 2012). Host immune responses to HSV-1 infection, like those to other viral infections, are complex.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal productions of type I IFNs are crucial for maintaining immune homeostasis and elimination of invading viruses (18,19). Thus, type I IFN secretion must be tightly controlled.…”
Section: Discussionmentioning
confidence: 99%